High aldehyde dehydrogenase activity at diagnosis predicts relapse in patients with t(8;21) acute myeloid leukemia - Yang, Lu (Cancer Med, 2019)
Acute myeloid leukemia (AML) with t(8;21) is a heterogeneous disease. Although the detection of minimal residual disease (MRD), which is indicated by RUNX1‐RUNX1T1 transcript levels, plays a key role in directing treatment, risk stratification needs to be improved, and other markers need to be assessed. A total of 66 t(8;21) AML patients were tested for aldehyde dehydrogenase (ALDH) activity by flow cytometry at diagnosis, and 52 patients were followed up for a median of 20 (1‐34) months. The median percentage of CD34+ALDH+, CD34+CD38‐ALDH+, and CD34+CD38+ALDH+ cells among nucleated cells were 0.028%, 0.012%, and 0.0070%, respectively. The CD34+ALDH+‐H, CD34+CD38‐ALDH+‐H, and CD34+CD38+ALDH+‐H statuses (the percentage of cells that were higher than the individual cutoffs) were all significantly associated with a lower 2‐year relapse‐free survival (RFS) rate in both the whole cohort and adult patients (P = .015, .016, and .049; P = .014, .018, and .032). Patients with < 3‐log reduction in the RUNX1‐RUNX1T1 transcript level after the second consolidation therapy (defined as MRD‐H) had a significantly lower 2‐year RFS rate than patients with ≥ 3‐log reduction (MRD‐L) (P = .017). The CD34+ALDH+ status at diagnosis was then combined with the MRD status. CD34+ALDH+‐L/MRD‐H patients had similar 2‐year RFS rates to both CD34+ALDH+‐L/MRD‐L and CD34+ALDH+‐H/MRD‐L patients (P = .50 and 1.0); and CD34+ALDH+‐H/MRD‐H patients had significantly lower 2‐year RFS rate compared with CD34+ALDH+‐L and/or MRD‐L patients (P < .0001). Multivariate analysis showed that CD34+ALDH+‐H/MRD‐H was an independent adverse prognostic factor for relapse. In conclusion, ALDH status at diagnosis may improve MRD‐based risk stratification in t(8;21) AML, and concurrent high levels of CD34+ALDH+ at diagnosis and MRD predict relapse.